Association between residential proximity to municipal solid waste incinerator sites and birth outcomes in Shanghai: a retrospective cohort study of births during 2014–2018. Issue 11 (2nd November 2022) - Hao, Yanhui; Wu, Weibin; Fraser, William D.; Huang, Hefeng
ABSTRACT: We tested the hypothesis of whether maternal residential proximity to municipal solid waste incinerator (MSWI) sites could significantly affect birth outcomes. This retrospective birth cohort study conducted at the International Peace Maternity and Infant Hospital, Shanghai, China, included 59, 606 mothers with singleton live births during 2014–2018. Multivariate generalized linear models were used to examine associations between residential proximity to MSWI sites and birth outcomes. Small for gestational age (SGA) was significantly more common among children with maternal residential proximity to MSWI sites (odds ratio [OR]=1.20, 95% confidence interval [CI]: 1.07–1.34). Maternal prepregnancy body mass index (BMI) influenced this association. Infants of underweight mothers (prepregnancy BMI <18.5 kg/m2) with MSWI exposure (OR=2.00, 95% CI: 1.58–2.52) had higher risks of SGA than their counterparts. Our findings underscore the need to prevent adverse environmental effects of MSWI on birth outcomes; improved exposure assessment measures are warranted in future studies.